PREVENTION MotilAeromonas Septicemia (MAS) of Pangasius hypophthalmus by SOLUTION Citrus hystrix - Santa, Santa; Riauwaty, Morina; Syawal, Henni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTCitrus hystrix is natural ingredient that was potentially being antimicrobial, because having many flavonoid, tannin and alkaloid compounds. The aim of this study was to get the best doses of solution Citrus hystrixto prevent MAS seen by leukocyte changes of Pangasiushypopthalmusso that it can be applied to fish affected by MAS disease. The method used of this study was Complete Random Match (CRD) with 1 factor, 5 treatments and 3 replications. NamelyKn negative control (without soaking solution Citrus hystrixand not challengedbyAeromonas hydrophila), Kp positive control (soaking solution Citrus hystrixand challengedbyAeromonas hydrophila), P1 soaking solution Citrus hystrixby 1200 ppm and challengedbyAeromonas hydrophila, P2 soaking solution Citrus hystrixby 1500 ppm and challengedbyAeromonas hydrophila,P3soaking solution Citrus hystrixby1800  ppm and challengedbyAeromonas hydrophila. Prevention by soaking for 2 minutes and done 4 times with interval of 7 days.Pangasiushypopthalmusused with 6-12 cm of size and 150 fishes. The study showed that soaking solution Citrus hystrixwith 1500 ppm of dose increased Pangasiushypopthalmushealth, seen by 10,26x104cells/mm3of leukocyte averages, leukocyte differentiations (85,67 ofLymphocytes, 5,67% ofneutrophils, 5,67% ofmonocytes,37,00%of phagocyte activities, 100%of survival rate dan 11,33 g of absolute weight growth. Keyword : Leukocyte, Pangasius hypophthalmus, Citrus hystrix,Aeromonas  hydrophila, Soaking